Comparison of the Effectiveness of Audio and VisualAudio as Health Promotion Media for Prevention of COVID-19 Transmission - Lina Eta Safitri; Desy Fadilah Adina Putri; Julia Mujahadah Pratiwi (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The elementary school (SD) in Jotang village in Sumbawa is a mountainous and coastal area with middle to lower economic status and the lack of availability of health workers there, allowing public knowledge, especially children, to be very lacking. There has never been any research on children's health in the area to be considered in choosing an elementary school in Jotang village to be the research site. This study aims to compare the effect of health promotion using audio media with audio-visual media on preventing the transmission of the COVID-19 virus to elementary school students in Jotang Village, Sumbawa RegencySubjects and Method: This research is a quasi-experimental study with pre-test and post-test designs. The research was conducted in Jotang village, Sumbawa regency, West Nusa Tenggara, Tahun 2022. The sample was 88 students. Variables The dependent variable was knowledge. The independent variables ware audio media and video media. Data were collected by using a questionnaire and analyzed by bivariate analysis with Mann Whitney test. Results: That audio-visual media is more effective than audio media as a health promotion medium for elementary school children compared to audio media with p= 0.039.Conclusion: Audio-visual media is more effective than audio media as a health promotionKeywords: health promotion media, COVID-19, primary school.Correspondence:Lina Eta Safitri. School of Health Sciences Griya Husada Sumbawa. Jl. Kebayan, Brang Biji, Sumbawa, West Nusa Tenggara. Email: Safitrieltalina96@gmail.com. Mobile: +6285337037619.Journal of Health Promotion and Behavior (2023), 08(01): 8-12DOI: https://doi.org/10.26911/thejhpb.2023.08.01.02